The role of institutional and policy frameworks in biodiversity offsets in South Africa: a review of offset frameworks - Mudzamiri, Maybe (My University, 2022)
The study investigated the effectiveness of institutional and policy frameworks in promoting successful biodiversity offsetting in South Africa. It argues that the success of biodiversity offsets is hinged on functional institutional and policy frameworks. Biodiversity offsets come as a way to facilitate sustainable developments by ensuring that any biodiversity loss is compensated. The study identified challenges and ways to pursue biodiversity offsets to create a baseline for sustainable development in a country where biodiversity offsets have been implemented for more than a decade without a comprehensive national biodiversity offset policy. The study engaged with literature obtained from globally accepted scientific databases and conducted interviews with industry experts to achieve this. Thematic content analysis was used to analyse that data. The data were codedusing a computer data analysis programme called QDA Miner. The findings suggest that despite the provisions for biodiversity offsets in South Africa’s legislation, there remain challenges in the offsetting process. These include weak institutional frameworks, the absence of an explicit national biodiversity offset policy, resistance to offsets, and land acquisitioni ssues, among other things. These challenges have made it difficult to develop an effective biodiversity offsetting strategy. The study also discovered that South Africa aligns in principle to the international standardsand has adopted the target-based ecological compensation approach in its draft offset policy. However, the mitigation hierarchy is not strictly adhered to, and there is a lack of clarity and guidance on remediation and offsetting agricultural activities, among other things, in the legislation. Some of the recommendations to address the identified challenges included formulating a comprehensive policy supported by a strong biodiversity offsets unit, conducting awareness campaigns forthe general public, educating practitioners and regulators, and conducting more scientific research. The study forms a basis for improved biodiversity offsetting in the country and can potentially inform other developing countries in a similar situation.
A research report submitted to the Faculty of Science, University of Witwatersrand, in partial fulfilment of the requirements for the degree Master of Science (Environmental Science,) 2022